A neighborhood museum for Barrios Altos Ecomuseums: drivers of community development - De Orellana Rojas, Juan (2019)
Los Barrios Altos is the most traditional area of Lima - outside Rímac (or Under the Bridge) in Lima Historic Center, World Heritage. Over the last years, it has been threatened by its gradual destruction to give way to huge pseudo-architectural buildings used as warehouses or to maintain trade in Gamarra and in Chinatown. To face this physical loss and the gradual loss of people’s identity, the idea of a Museo del Vecindario (Neighborhood Museum), proposed to the Metropolitan Municipality of Lima 15 years ago, reappears. This would become an ecomuseum, where people could discuss their concerns, recover and revalidate their self-esteem and self-worth so as to generate development for themselves, from themselves.This only requires the will and decision of the Municipality as well as the collaboration of an academic entity that follows the research and advises the population suitably. The idea is that it should be highly participative, and that the voice of the citizen self-government of this population could arise from this ecomuseum -almost like the medieval town halls. In this way, people would recover their cultural heritage, in general, but especially their intangible cultural heritage